2013
DOI: 10.12806/v12/i2/r4
|View full text |Cite
|
Sign up to set email alerts
|

Using Involvement Theory to Examine the Relationship between Undergraduate Participation in Extracurricular Activities and Leadership Development

Abstract: This study examined the relationship between extracurricular involvement and leadership outcomes among traditional-age college seniors in the College of Agriculture and Life Sciences at Iowa State University. We collected data related to quantitative (i.e., how much time a student spends on an activity) and qualitative (i.e., how focused the student is on the activity) aspects of involvement in extracurricular organizations. We measured leadership, as an outcome, using the individual values scale of the Social… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 19 publications
(38 reference statements)
2
18
2
Order By: Relevance
“…As for the average number of activities performed by the students, Universidade do Estado do Pará presented a higher average (2 actives/student), agreeing with the findings of Roulin and Bangerter 20 , who observed predominance of students performing 2 extracurricular activities. However, they differ from the studies of Foreman and Retallick 21 , at Iowa State University (USA), which identified an average activity of 3.41 ativ. /student.…”
Section: Discussioncontrasting
confidence: 96%
See 1 more Smart Citation
“…As for the average number of activities performed by the students, Universidade do Estado do Pará presented a higher average (2 actives/student), agreeing with the findings of Roulin and Bangerter 20 , who observed predominance of students performing 2 extracurricular activities. However, they differ from the studies of Foreman and Retallick 21 , at Iowa State University (USA), which identified an average activity of 3.41 ativ. /student.…”
Section: Discussioncontrasting
confidence: 96%
“…Similarly, it resembles a study conducted by Roulin and Bangerter 20 , with students from a Swiss university, which showed that 80.2% of these were involved in this type of activity. However, it diverges from other surveys, which found higher percentages 9,15,16,21 . These findings show that health professional training program students' participation in extracurricular activities surpass those pre-established by the universities, evidencing their autonomy and proactivity, important issues for future professionals.…”
Section: Discussioncontrasting
confidence: 96%
“…Leadership development concepts for college students, both in and out of the classroom, have been reflected in the literature for years (Keeling, 2004). In a study by Foreman and Retallick (2013), students who held a leadership position in a student organization scored significantly higher on the scales of consciousness of self, commitment, and individual values on the Socially Responsible Leadership Scale. Rubin, Bommer, and Baldwin (2002) reported that an extracurricular index score indicating the number of student organizations, leadership roles, and hours spent in those organizations significantly predicted development of skills such as communication, initiative, decision making, and teamwork.…”
Section: Leadership Developmentmentioning
confidence: 95%
“…Involvement is frequently captured as a binary variable indicating participation or not; however, several studies have noted Astin's specification of quality and quantity in his theory of involvement and sought to capture some extent of involvement in reflection of quality and/or quantity. Common extensions of the participation variable seek to measure some aspect of frequency or time allocated to involvement in student organizations [42], [58]. For example, Foreman & Retallick [42] analyzed students' leadership development with respect to the number of organizations in which they participated, the average number of hours per week they reported spending in clubs and organizations, and whether they held a leadership role in any clubs.…”
Section: Rq1mentioning
confidence: 99%
“…Common extensions of the participation variable seek to measure some aspect of frequency or time allocated to involvement in student organizations [42], [58]. For example, Foreman & Retallick [42] analyzed students' leadership development with respect to the number of organizations in which they participated, the average number of hours per week they reported spending in clubs and organizations, and whether they held a leadership role in any clubs. Additionally, the College Student Experiences Questionnaire [59], which later informed the National Survey of Student Engagement [12], incorporated questions about the quality of students' experiences in student organizations.…”
Section: Rq1mentioning
confidence: 99%